Impact of Gadget Games on Stress During Hospitalization in Preschool Children - Chanafi, Imam; Yulianti, Eny; Palufi, Ulfa Engky (Dewan Pimpinan Daerah Persatuan Perawat Nasional Indonesia Kota Blitar, 2023)
Hospitalization is a threatening experience for children and can cause stress. Reducing the stress level of children due to hospitalization varies greatly, one of which is play therapy. Currently, the style of play of children has changed a lot. In this modern era, children's playing styles have experienced a transition from traditional games to more modern ones. One of them is playing games on gadgets. The purpose of this study was to determine the effect of playing game therapy on gadgets on stress due to hospitalization in preschool-aged children. The research design used was Quasy Experiment (one group pre-post test design) with a sample of 22 respondents from a population of 28 children taken by purposive sampling method. Data collection used a stress questionnaire on hospitalization in preschool-aged children. In analyzing the data using the Wilcoxon test, the results obtained were p = 0.000, which means that there was a difference between before being given game therapy and after being given game therapy. From the results of this study it is hoped that it can provide innovation and development for educational institutions, nurses and other medical personnel in providing play therapy for children that can be played easily so that it can reduce the stress caused by hospitalization experienced by children.